Daily Variations in the Glycerol-3-Phosphate Dehydrogenase isoforms expression in Triatoma infestans flight muscles - Stroppa, Maria Mercedes (2014)
Triatoma infestans, the main vector of Chagas disease, is a blood-sucking insect. Flight dispersal of adults is the most important mechanism for reinfestation of houses after insecticide spraying. Flight muscles have two glycerol-3-phosphate dehydrogenase (GPDH) isoforms: GPDH-1 is involved in flight metabolism and GPDH-2 provides lipid precursors. In this study, we explored the profile of GPDH expression in females and males adult flight muscles under light/dark cycle, constant light, and constant dark conditions. Under constant dark conditions, GPDH-1 flight muscles of T. infestans showed a rhythmic pattern of transcription synchronous with a rhythmic profile of activity suggesting regulation by the endogenous circadian clock. Otherwise, the GPDH-2 expression analysis showed no regulation by the endogenous clock, but showed that an external factor, such as the dark/light period, was necessary for synchronization of GPDH-2 transcription and activity.